2016
DOI: 10.1097/md.0000000000004536
|View full text |Cite
|
Sign up to set email alerts
|

Association between comorbid conditions and BADL/IADL disability in hypertension patients over age 45

Abstract: Hypertension usually coexists with other chronic conditions and can cause disability in relation to activities of daily living. We examined the association between the number and categories of comorbid conditions and disability affecting activities of daily living in hypertension patients.The data were collected from the 2013 follow-up survey of the China Health and Retirement Longitudinal Study (CHARLS), which contains information about chronic conditions and disability. Additionally, socio-demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
(34 reference statements)
5
27
0
4
Order By: Relevance
“…In line with other studies, age was identified as a major risk factor for a decline in IADL functioning (27–29). Even though we noticed a more prominent age effect on the decline in several IADL activities for persons with “no MCC” at inclusion, we were able to confirm the findings of other studies that multimorbidity imposes a risk for decline in IADL functioning (5,7,28,29). The trends illustrated that persons with “≄3 MCC” and “1–2 MCC” had higher levels of disability at inclusion that progressed over time with higher risks of disability in late life for the majority of activities.…”
Section: Discussionsupporting
confidence: 87%
“…In line with other studies, age was identified as a major risk factor for a decline in IADL functioning (27–29). Even though we noticed a more prominent age effect on the decline in several IADL activities for persons with “no MCC” at inclusion, we were able to confirm the findings of other studies that multimorbidity imposes a risk for decline in IADL functioning (5,7,28,29). The trends illustrated that persons with “≄3 MCC” and “1–2 MCC” had higher levels of disability at inclusion that progressed over time with higher risks of disability in late life for the majority of activities.…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies have shown that chronic multimorbidity is an established risk factor for disability [26][27][28][29]34]. Based on the data from the CHARLS (2013), Qian et al confirmed that chronic multimorbidity was associated with a 3.66-fold increased risk of disability in ADLs and a 2.00-fold increased risk of disability in IADLs among adults aged ≄ 45 years who had hypertension [35]. However, the contribution of SMM to disability was understudied in this study.…”
Section: Discussionsupporting
confidence: 48%
“…Diseases having clear manifestations of physical symptoms impact the activity of daily living of a patient more, than diseases like hypertension and diabetes. It is evident that, such physical symptoms like pain in joints or breathing problem affects an individual’s activities thus impairing the quality of life[ 49 ]. Our study also reveals the high functional limitation accruing from musculoskeletal disorders, which advocates for availability for the musculoskeletal care in primary care setting in India.…”
Section: Discussionmentioning
confidence: 99%